Local control and possibility of tailored salvage after hypofractionated stereotactic radiotherapy of the cavity after brain metastases resection - Angelika Bilger; Eva Bretzinger; Jamina Fennell; Carsten Nieder; Hannah Lorenz; Oliver Oehlke; Anca‐Ligia Grosu; Hanno M. Specht; Stephanie E. Combs (Cancer Medicine)
Abstract In patients undergoing surgical resection of brain metastases, the risk of local recurrence remains high. Adjuvant whole brain radiation therapy (WBRT) can reduce the risk of local relapse but fails to improve overall survival. At two tertiary care centers in Germany, a retrospective study was performed to evaluate the role of hypofractionated stereotactic radiotherapy (HFSRT) in patients with brain metastases after surgical resection. In particular, need for salvage treatment, for example, WBRT, surgery, or stereotactic radiosurgery (SRS), was evaluated. Both intracranial local (LF) and locoregional (LRF) failures were analyzed. A total of 181 patients were treated with HFSRT of the surgical cavity. In addition to the assessment of local control and distant intracranial control, we analyzed treatment modalities for tumor recurrence including surgical strategies and reirradiation. Imaging follow‐up for the evaluation of LF and LRF was available in 159 of 181 (88%) patients. A total of 100 of 159 (63%) patients showed intracranial progression after HFSRT. A total of 81 of 100 (81%) patients received salvage therapy. Fourteen of 81 patients underwent repeat surgery, and 78 of 81 patients received radiotherapy as a salvage treatment (53% WBRT). Patients with single or few metastases distant from the initial site or with WBRT in the past were retreated by HFSRT (14%) or SRS, 33%. Some patients developed up to four metachronous recurrences, which could be salvaged successfully. Eight (4%) patients experienced radionecrosis. No other severe side effects (CTCAE≥3) were observed. Postoperative HFSRT to the resection cavity resulted in a crude rate for local control of 80.5%. Salvage therapy for intracranial progression was commonly needed, typically at distant sites. Salvage therapy was performed with WBRT, SRS, and surgery or repeated HFSRT of the resection cavity depending on the tumor spread and underlying histology. Prospective studies are warranted to clarify whether or not the sequence of these therapies is important in terms of quality of life, risk of radiation necrosis, and likelihood of neurological cause of death.